Development Patterns: An Interregional Study - Gupta, Kanhaya L. (Quarterly Journal of Economics, 1971)
I. The data and the models, 645. — II. The results of cross-section equations, 646. — III. Residuals from group regressions, 659. — IV. Over time variation, 660. — V. Balanced versus unbalanced growth, 662. — VI. Conclusions, 666.